2020
DOI: 10.1101/2020.01.13.903963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Domain segregated 3D chromatin structure and segmented DNA methylation in carcinogenesis

Abstract: The three-dimensional (3D) chromatin structure, together with DNA methylation and other epigenetic marks, profoundly affects gene expression and displays abnormal behaviors in cancer cells. We elucidated the chromatin architecture remodeling in carcinogenesis from the perspective of spatial interactions between CGI forest and prairie domains, which are two types of megabase-sized domains defined by different sequence features but show distinct epigenetic and transcriptional patterns. DNA sequence strongly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
3
4
0
Order By: Relevance
“…Xuan Ming et al also found that solo-WCGW sites display aging-and cancer-associated hypomethylation, which exhibits low maintenance efficiency during the cell cycle [37]. For chromatin structural changes, we compared the segregation ratio in the G1 stage to that in the late S~G2 stage, and found that forests and prairies tend to become more separated in the late S~G2 stage [35]. The enhanced segregation supports the hypothesis that mitosis is conducive to a more segregated chromatin structure.…”
Section: The Association Between Domain Segregation and Dna Methylationsupporting
confidence: 70%
See 1 more Smart Citation
“…Xuan Ming et al also found that solo-WCGW sites display aging-and cancer-associated hypomethylation, which exhibits low maintenance efficiency during the cell cycle [37]. For chromatin structural changes, we compared the segregation ratio in the G1 stage to that in the late S~G2 stage, and found that forests and prairies tend to become more separated in the late S~G2 stage [35]. The enhanced segregation supports the hypothesis that mitosis is conducive to a more segregated chromatin structure.…”
Section: The Association Between Domain Segregation and Dna Methylationsupporting
confidence: 70%
“…Earlier studies have found that DNA hypomethylation, which is more likely to occur in prairie domains, correlates with the cell cycles. Partially methylated domains (PMDs) in tumor cells are mainly composed of prairies [35], and PMD hypomethylation increases with age, which appears to track the accumulation of cell divisions [36]. Xuan Ming et al also found that solo-WCGW sites display aging-and cancer-associated hypomethylation, which exhibits low maintenance efficiency during the cell cycle [37].…”
Section: The Association Between Domain Segregation and Dna Methylationmentioning
confidence: 99%
“…Xuan Ming et al also found that solo-WCGW sites display aging- and cancer-associated hypomethylation, which exhibit low maintenance efficiency during cell cycle(Ming et al, 2020). For chromatin structural changes, we compared the segregation ratio in G1 stage to that in the late S ~ G2 stage, and found that forest and prairie tend to become more separated in the late S ~ G2 stage (the related figure can be found in Xue et al, 2020). The enhanced segregation supports that mitosis is conducive to a more segregated chromatin structure.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have found that DNA hypomethylation, which is more likely to occur in prairie domains, correlates with the cell cycles. Partially methylated domains (PMDs) in tumor cells are mainly composed of prairies (Xue et al, 2020) and PMD hypomethylation increases with age, which appears to track the accumulation of cell divisions (Zhou et al, 2018). Xuan Ming et al also found that solo-WCGW sites display aging-and cancerassociated hypomethylation, which exhibit low maintenance efficiency during cell cycle (Ming et al, 2020).…”
Section: Domain Segregation and Differentiated Dna Methylation Associated With Germ Layer Formationmentioning
confidence: 99%
“…Xuan Ming et al also found that solo-WCGW sites display aging- and cancer-associated hypomethylation, which exhibit low maintenance efficiency during cell cycle(Ming et al, 2020). For chromatin structural changes, we compared the segregation ratio in G1 stage to that in the late S ~ G2 stage, and found that forest and prairie tend to become more separated in the late S ~ G2 stage (Xue et al, 2020). The enhanced segregation supports that mitosis is conducive to a more segregated chromatin structure.…”
Section: Resultsmentioning
confidence: 99%